2017
DOI: 10.5539/jel.v7n1p53
|View full text |Cite
|
Sign up to set email alerts
|

The Emphasis of Inquiry Instructional Strategies: Impact on Preservice Teachers’ Mathematics Efficacy

Abstract: Using a Mixed Methods approach, this study investigated changes in levels of self-efficacy among elementary preservice teachers following a semester course on teaching elementary students’ mathematics. Participants in this study included 347 preservice elementary teachers at a mid-size regional university who had just completed an elementary mathematics methods course. The data were collected from several semester groups. The instruments used were the Mathematics Teaching Efficacy Beliefs Instrument, interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…As an organizational tool, the codes have been presented in the alphabetical order of the authors of the study. For example, in reading Althauser's (2018) study, the code "belief" emerged which also appeared in Fletcher and Luft's (2011) study. An excerpt from Fletcher and Luft's (2011) study "Teacher beliefs fluctuated depending upon the level of practical field experience of the teacher as well as the focus of instructor for the course" (p. 1143) was used for the example because this statement generated more than one code.…”
Section: Exclusion Criteriamentioning
confidence: 89%
See 3 more Smart Citations
“…As an organizational tool, the codes have been presented in the alphabetical order of the authors of the study. For example, in reading Althauser's (2018) study, the code "belief" emerged which also appeared in Fletcher and Luft's (2011) study. An excerpt from Fletcher and Luft's (2011) study "Teacher beliefs fluctuated depending upon the level of practical field experience of the teacher as well as the focus of instructor for the course" (p. 1143) was used for the example because this statement generated more than one code.…”
Section: Exclusion Criteriamentioning
confidence: 89%
“…To implementing the 5E instructional model ◊ Belief (Althauser, 2018;Fletcher & Luft, 2011;Smolleck and Mongan, 2011) ◊ Content (Bozdogan & Altuncekic, 2007;Celik et al, 2018;Demirbas & Pektas, 2015;Metin & Ozmen, 2009) ◊ Materials (Bozdogan & Altuncekic, 2007;Celik et al, 2018;Metin et al, 2011;Metin & Ozmen, 2009;Smolleck & Mongan 2011;Polgampala et al, 2016) ◊ Classroom Management (Bozdogan & Altuncekic, 2007;Celik et al, 2018;Enugu & Hokayem, 2017;Smolleck & Mongan 2011;Polgampala et al, 2016) ◊ Time (Bozdogan & Altuncekic, 2007;Celik et al, 2018;Demirbas & Pektas, 2015;Enugu & Hokayem, 2017;Fletcher & Luft, 2011;Metin et al, 2011;Metin & Ozmen, 2009;Smolleck & Mongan 2011;Polgampala et al, 2016) ◊ Subject (Demirbas & Pektas, 2015 ;Metin et al, 2011 ;Polgampala et al, 2016). ◊ Colleagues (Enugu & Hokayem, 2017;Fletcher & Luft, 2011 ;Smolleck and Mongan, 2011) T: ...can be applied to science education but I think it is very difficult to be applied to social studies (Polgampala et al, 2016, p. 40).…”
Section: Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…While many factors could cause this lack of adoption, teachers' selfefficacy is one factor that has been widely studied related to teachers' intentions. Several studies have reported that teachers' self-efficacy have been identified to affect teachers' motivation to adopt new teaching methods, especially in cases where there is already a positive attitude (Althauser, 2018;Caraway, Tucker, Reinke, & Hall, 2003;Silm, Tiitsaar, Pedaste, Zacharia, & Papaevripidou, 2017). Silm et al (2017) found teachers' unwillingness to engage in inquiry-based learning (IBL) was due to low self-efficacy as a result of a lack of requisite knowledge that is necessary to implement the instructional strategy in their classrooms.…”
Section: Introductionmentioning
confidence: 99%